Adherence to Traditional Chinese Postpartum Practices and Postpartum Depression: A Cross-Sectional Study in Hunan, China - Guo, Pengfei; Xu, Dong; Liew, Zeyan; He, Hua; Brocklehurst, Peter; Taylor, Beck; Zhang, Chao; Jin, Xin; Gong, Wenjie (Frontiers in Psychiatry, 2021)
Background: The relationship between adherence to traditional Chinese postpartum practices (known as ‘doing-the-month’) and postpartum depression (PPD) remains unknown. Practices including restrictions on diet, housework and social activity, personal hygiene, and cold contact, could introduce biological, psychological and socio-environmental changes during postpartum. Methods: The cross-sectional study included 955 postpartum women in obstetric clinics in Hunan Province of China between September 2018 to June 2019. Thirty postpartum practices were collected by a self-report online structured questionnaire. PPD symptoms were assessed by the Chinese version of the Edinburgh Postnatal Depression Scale (EPDS). Multivariable linear regression was used to estimate the differences in EPDS scores according to adherence to postpartum practices. Firth’s bias-reduced logistic regression was employed to analyze the binary classification of having PPD symptoms (EPDS >=10). Results: Overall, both moderate and low adherence to postpartum practices appeared to be associated with higher EPDS scores (adjusted difference 1.07, 95%CI 0.20, 1.94 for overall moderate adherence; and adjusted difference 1.72, 95%CI 0.84, 2.60 for overall low adherence). In analyses by practice domain, low adherence to housework-related and social activity restrictions was associated with having PPD symptoms compared with high adherence (OR 1.61, 95%CI 1.07, 2.43). Conclusions: Low adherence to traditional Chinese postpartum practices was associated with higher EPDS scores indicating PPD symptoms, especially in the domain of housework-related and social activity restrictions. Psychosocial stress and unsatisfactory practical support related to low adherence to postpartum practices might contribute to PPD. Longitudinal study and clinical assessment would be needed to confirm these findings.